Patterns of sport participation for youth with autism spectrum disorder and intellectual disabilities. Issue 3 (4th October 2017) - Ryan, Stephanie; Fraser‐Thomas, Jessica; Weiss, Jonathan
Abstract : Background: Little is known about sport participation in youth with Autism Spectrum Disorder (ASD). The current study examined sport characteristics (frequency, diversity, positive social experiences [PSE]) for youth with ASD and intellectual disability compared to youth with intellectual disability alone and explored the personal and contextual correlates of involvement. Method: Parents ( N  = 409) completed an online survey, and multiple mediation analyses were used to examine the factors that explained the relationships between sport involvement in youth with ASD and intellectual disability. Results: No significant main effects of ASD status were found for frequency or diversity, but youth with intellectual disability alone had higher scores for PSE compared to youth with ASD and intellectual disability. Sociocommunicative abilities, coach relationship and resources mediated the relationship between ASD status and PSE. Conclusions: A better understanding of the factors related to sport is essential for allowing families, service providers and policy makers to improve involvement for youth with ASD.